Pembentukan Karakter Anak Melalui Keteladanan Orang Tua - Christianty, Orient; Loho, Margarith Iriana (Peneliti.net, 2023)
Parental examples have an important role in shaping a child's character. This research aims to examine the formation of children's character through parental examples. The method in this research uses literature study. The literature used is 10 scientific journals that have been published and 10 books related to the formation of children's character and parental example. The results of this research are that children are great imitators, so parental examples are important in forming children's character. Children are great imitators, they do what they see. Children are greatly influenced not only by their parents' words but also their actions. In their lives, children see and experience life with their parents directly. This research complements previous research, by examining the basic characters and characteristics of children.